Soaring Spain: A Dream Deferred? - Rumbley, Laura E; Howard, Laura (International Higher Education, 2014)
Universities in Spain were committed to an active internationalization agenda with government initiatives such as Estrategia Universidad 2015 and Universidad.es set to help them along this path. However, the current economic crisis has dramatically slowed down this process. Spain’s continued success in attracting international students may keep the momentum going.